Mandated to fail? Humanitarian agencies and the protection of Palestinian children. Issue 4 (6th September 2013) - Hart, Jason; Forte, Claudia Lo
Abstract : This paper considers the efforts of United Nations and international agencies to address the threats to Palestinian children arising from Israeli occupation. It contains an account of the reasons why agencies have failed, over many years, to prevent systematic violations by the Israeli authorities and settlers. The discussion is organised around two inter‐related domains: institutional and political. The paper argues that, in the occupied Palestinian territory (oPt), limitations to the ways in which child protection has been conceptualised and pursued in practice are abundantly evident. Nevertheless, political pressure by Western donor governments serves to constrain an approach to child protection that is more preventative in nature, that addresses more explicitly Israeli violations of international law, and that reflects the experience and aspirations of Palestinian children themselves. Ultimately, therefore, the failure to protect Palestinian children must be seen not only as a result of humanitarian miscalculation but also as a consequence of political strategy.